Intervention experience Physiotherapy in assisted living facilities for the elderly (Cuestiones de Fisioterapia, 2005)
With the following work, one tries to increase the field of intervention of the physical therapy in geriatrics showing for it the importance of a treatment where not only there lends attention to the physical aspect of the health, but also to the cognitive deterioration that there present the persons of advanced age, as well as the social slope that meets affected after the revenue in a center or residence.One proposes a treatment that includes physical exercise, cognitive stimulation and social relation and with the way to which one belongs(concerns), and there is demonstrated that it is possible to obtain benefit in ail the areas of the health, promoting with it the need of a complete intervention on the part of the figure of the physical therapy.